The analysis of poisonings treated at the Department of Toxicology in Rzeszów in 2011–2013 - Filip, Dawid; Kucaba, Grzegorz; Załucka, Jadwiga; Ozga, Dorota; Wojtaszek, Marek (European Journal of Clinical and Experimental Medicine, 2015)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. The number of accidents and emergencies, among them poisonings, is currently increasing rapidly. Both accidental and intentional exposure to toxic substances is not only the problem of toxicology departments but also emergency medical system. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim of study. The aim of the study was to analyze poisonings in terms of a type and severity among the patients treated at the Department of Toxicology of St. Hedvig Provincial Hospital No.2 in Rzeszów in 2011-2013 and factors affecting the incidence of poisonings. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The study analyzed cumulative statistics from a hospital department on intoxicated patients. Sex, age, type and severity of poisoning, effect of therapy, the way of admission and discharge were collected from the available data. All graphs and tables in the paper were elaborated by means of IBM SPSS Statistic software. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The number of patients treated for poisoning in the branch increased during researched period from 332 to 491. Men were hospitalized more often than women and the most common cause of the stay was ethanol poisoning or other conditions associated with alcohol abuse. The increase in the number of severe poisonings in the subsequent years from 5.12% in 2011 to 11% in 2013 was observed. The increase in the number of patients referred for further treatment to another hospital was also noted. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusions.The increase in the number of hospitalized patients and the severity of poisonings was found. The men were more often prone to poisonings and the most common reason of poisoning was ethyl alcohol. A very small percentage of the poisonings was fatal. More than a half of intoxicated patients had comorbidities. Most frequently patients were transported to the emergency department and the department of toxicology by emergency medical service.